2004
DOI: 10.1097/01.mjt.0000117501.97441.c92004
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Tract Diseases Revealed after DTP Vaccination in Infants and Young Children

Abstract: Prophylactic vaccinations may sometimes shorten the incubation period of some illnesses and/or convert a latent infection/inflammation into a clinically apparent disease. Cytokines play a major role in mediating the inflammatory process in various clinical entities and represent a potential source of tissue damage if their production is not sufficiently well controlled. It seems that irregularities in production of proinflammatory cytokines may be responsible for the abnormalities associated with full-blown cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…It has been reported that some infants and young children develop various urinary tract diseases, such as acute renal failure, nephrotic syndrome, or pyelonephritis, after the injection of the whole-cell DTP vaccine [363]. Administration of DTP vaccine caused dose-, and time-dependent biological changes in animals, including increased hepatic mRNA expression for several cytokines, marked inhibition of liver CYP450 enzymes activity, induction of IFN-γ, and enhanced NOS mRNA expression [364], [365].…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that some infants and young children develop various urinary tract diseases, such as acute renal failure, nephrotic syndrome, or pyelonephritis, after the injection of the whole-cell DTP vaccine [363]. Administration of DTP vaccine caused dose-, and time-dependent biological changes in animals, including increased hepatic mRNA expression for several cytokines, marked inhibition of liver CYP450 enzymes activity, induction of IFN-γ, and enhanced NOS mRNA expression [364], [365].…”
Section: Resultsmentioning
confidence: 99%